Responsabilidad social empresarial en las cooperativas multiactivas de Barranquilla (2019)
Taking into account the needs of the cooperative sector, in our research we seek to strengthen corporate social responsibility in multi-activity cooperatives in the city, whose study showed that both internal and external dimensions are cooperatives have many flaws, which led us to evaluate each One of the indicators that is reflected in our research, it should be noted that this research is going to be socialized and shared with those cooperatives that opened the Door. To improve administrative matters and, above all, to become aware of the importance of corporate social responsibility in cooperatives with all their stakeholders